The vagaries of vulnerability - Wilkin, David (Disability hate crime, 2025)
Protecting the vulnerable. How many times do we hear this phrase? In the media, in general conversation, among safeguarding organisations. Vulnerability is perhaps an overused term. Whether we, ourselves, feel vulnerable or that term has been applied to us – with or without our consent – vulnerability as a concept predicts harm, stirs up emotion, and counteracts access to justice. This chapter describes how disabled people are feeling vulnerable, with the focus of this book being within the context of them being victims of hate and hostility shown towards them. There are three aspects of vulnerability discussed in this chapter: firstly, the harm predicted by feeling vulnerable. Victims of disability hate and the microaggressions which pervade the lives of people already disadvantaged are brought to light. The chapter then moves to illustrate the frustrations suffered by disabled people when they have tried to report that they have been victims of hate crimes and the denial of justice that is sometimes facilitated by the police as they are signposted to health or welfare organisations rather than processed into receiving justice. Finally, the media plays a part in all of this. We examine how the media uses vulnerability to inform or influence the public. The emotion that can be emphasised and utilised by the media can, arguably, play a role in managing our behaviours when it comes to understanding disabled victims.